Morphological Diversity of Calretinin Interneurons Generated From Adult Mouse Olfactory Bulb Core Neural Stem Cells - Fernández Acosta, Francisco J.; Luque-Molina, Inma; Vecino, Rebeca; Díaz-Guerra, Eva; Defterali, Çagla; Pignatelli, Jaime; Vicario, Carlos (Frontiers in Cell and Developmental Biology, 2022)
Neural stem cells (NSCs) in the olfactory bulb (OB) core can generate mature interneurons in the adult mice brain. The vast majority of these adult generated cells express the calcium-binding protein Calretinin (CalR), and they migrate towards different OB layers. However, these cells have yet to be fully characterized and hence, to achieve this we injected retroviral particles expressing GFP into the OB core of adult animals and found that the CalR+ neurons generated from NSCs mainly migrate to the granule cell layer (GCL) and glomerular layer (GL) in similar proportions. In addition, since morphology and function are closely related, we used three-dimensional imaging techniques to analyze the morphology of these adult born cells, describing new subtypes of CalR+ interneurons based on their dendritic arborizations and projections, as well as their localization in the GCL or GL. We also show that the migration and morphology of these newly generated neurons can be altered by misexpressing the transcription factor Tbr1 in the OB core. Therefore, the morphology acquired by neurons located in a specific OB layer is the result of a combination of both extrinsic (e.g., layer allocation) and intrinsic mechanisms (e.g., transcription factors). Defining the cellular processes and molecular mechanisms that govern adult neurogenesis might help better understand brain circuit formation and plasticity, as well as eventually opening the way to develop strategies for brain repair.